Estudo teórico de dopagem, adsorção e intercalação de vanádio em monocamada e bicamada de disseleneto de molibdênio - MoSe2 - Piero, João Vitor Bastos Del (2022)
In this dissertation, the results of computer simulations of two-dimensional structures using the density functional theory (DFT) will be presented. Doping, adsorption and intercalation studies of vanadium atoms in monolayers and bilayers of molybdenum dise lenide, MoSe2 will be carried out. The results obtained show that it is possible to control the electronic, structural and magnetic properties of the two-dimensional structures from the vanadium concentration to be considered in each of the proposed configurations. Among the observed changes, there is a reduction in the energy gap of the monolayer when doping with vanadium is performed, while in the bilayer there is the appearance of non-zero total magnetic moment magnetization and the variation of its final thickness when the doping and intercalation processes are carried out. For the bilayer it was found that both doping and intercalation are tools to control the magnetic properties of the material. In the other hand, for some structures it is possible to have the coexistence between the ferromagnetic and antiferromagnetic phases at room temperature, since the energy di↵erence between the phases did not exceed 20meV . Someof theseresults in dicate the possible application of such structures in electronics and spintronics devices.